Estudo morfológico das formas verbais do modo imperativo nas Cantigas de Santa Maria - Fávaro, Gisela Sequini [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study aims to map and analyze the morphological structure in the process of verb inflection of imperative forms in Archaic Portuguese (AP) in the Cantigas de Santa Maria (CSM). The objective of the study is to show if the situation we find today (i.e., variation among indicative and subjunctive forms to express orders and requests), which leads to the question if the imperative was an independent mood or not, already occurred in the AP. The methodology consists in mapping the imperative verb forms in the CSM. We have also used glossaries and vocabularies as a support in categorization of verb forms. After data is collected, the morphological structure of the imperative verb forms found are analyzed in comparison with the morphological structure of the simple present and subjunctive mapped in the corpus, in order to explain if criteria, such as order, presence or absence of the subject and contexts related to speech acts (order or request), can be used to consider if a form is imperative or not. One hundred eighty-nine imperative verb forms conjugated in the secondperson plural and second-person singular were collected and at the end of the analysis of the data we verified the high productivity of the suppression of the thematic vowel at an early stage of the language. We can prove that the imperative form preserved its morphological structure in the AP, since the variation indices start to emerge only in mid-eighteenth century, when there are the first manifestations of the process which replaces tu by você in treatment relations. We have also discussed, from a diachronic perspective, by the factors of linguistic and social nature that interfered and continue to interfere in the process of change in pronoun forms of address in BP and how this phenomenon is associated with the probable loss of the morphology of the imperative form. Thus, this thesis aimed to contribute to the history of the Portuguese language, considering that the resumption of facts of the linguistic past of the Portuguese language can bring greater understanding of the structure of the current Portuguese.

Este estudo objetiva realizar o mapeamento e a análise da estrutura morfológica no processo da flexão verbal das formas imperativas em Português Arcaico (PA), a partir das Cantigas de Santa Maria (CSM), com a finalidade de mostrar se a situação que encontramos hoje (ou seja, variação entre formas indicativas e subjuntivas para expressar ordens e pedidos), que leva à dúvida quanto ao imperativo ser um modo independente ou não, já ocorria no PA. A metodologia constitui-se no mapeamento das formas verbais do imperativo nas CSM. Contamos, também, com glossários e vocabulários como auxílio na categorização das formas verbais. Após a coleta dos dados, são analisadas as estruturas morfológicas das formas verbais imperativas encontradas, comparando-as com a estrutura morfológica das formas verbais do presente do indicativo e do subjuntivo mapeadas no corpus, a fim de explicar se critérios, tais como ordem, presença ou ausência do sujeito e contextos relacionados a atos de fala (ordem ou pedido), podem ser utilizados para considerar uma forma imperativa ou não. Foram coletadas 189 formas verbais imperativas conjugadas nas 2ªpp e 2ªps. Verificamos a alta produtividade da supressão da vogal temática em um estágio inicial da língua. Podemos comprovar que o modo imperativo preservava sua estrutura morfológica no PA, já que os indíces de variação começam a surgir apenas em meados do século XVIII, quando há as primeiras manifestações do processo de substituição do pronome tu por você nas relações de tratamento. Discorremos, também, a partir de uma perspectiva diacrônica, sobre os fatores de natureza linguística e social que interferiram e continuam interferindo no processo de variação das formas pronominais de tratamento em PB e como este fenômeno está associado à provável perda da morfologia do modo imperativo. Assim, esta tese visou a contribuir para a compreensão da história do português, no sentido de que a retomada de fatos do passado linguístico da língua portuguesa pode trazer uma maior compreensão da estrutura do português atual.
Morphological study of the verbal forms of the imperative mood in the Cantigas de Santa Maria
Keywords: Imperative mood; Archaic portuguese; Verbs; Morphology; Modo imperativo; Português arcaico; Cantigas de Santa Maria; Verbos; Morfologia